Oligodendroglial heterogeneity in health, disease, and recovery: deeper insights into myelin dynamics - Pieter-Jan Serneels; Julie D. De Schutter; Lies De Groef; Lieve Moons; Steven Bergmans (Neural Regeneration Research)
Decades of research asserted that the oligodendroglial lineage comprises two cell types: oligodendrocyte precursor cells and oligodendrocytes. However, recent studies employing single-cell RNA sequencing techniques have uncovered novel cell states, prompting a revision of the existing terminology. Going forward, the oligodendroglial lineage should be delineated into five distinct cell states: oligodendrocyte precursor cells, committed oligodendrocyte precursor cells, newly formed oligodendrocytes, myelin-forming oligodendrocytes, and mature oligodendrocytes. This new classification system enables a deeper understanding of the oligodendroglia in both physiological and pathological contexts. Adopting this uniform terminology will facilitate comparison and integration of data across studies. This, including the consolidation of findings from various demyelinating models, is essential to better understand the pathogenesis of demyelinating diseases. Additionally, comparing injury models across species with varying regenerative capacities can provide insights that may lead to new therapeutic strategies to overcome remyelination failure. Thus, by standardizing terminology and synthesizing data from diverse studies across different animal models, we can enhance our understanding of myelin pathology in central nervous system disorders such as multiple sclerosis, Alzheimer’s disease, and amyotrophic lateral sclerosis, all of which involve oligodendroglial and myelin dysfunction.